Improving Sound Insulation in Low Frequencies by a Three-Component Cladding Acoustic Metamaterial Panel - TAN, Na; YAN, Xiaowei; LIU, Bingfei (Archives of Acoustics, 2024)
In this paper, a three-component cladding acoustic metamaterial panel with good sound insulation effect in the low-frequency range is proposed. The sound transmission loss of metamaterial panels under different structural configurations and different material parameters is investigated by combining finite element simulation calculations with experimental research. The results show that the closer the center of gravity of the scatterer is to the substrate, the better the stability of the resonance unit, the wider the range of effective sound isolation frequencies, and the higher the degree of normalization. The filling rate of the scatterer is maintained at about 0.5 to obtain a better sound insulation effect. At the same time, choosing lower density materials for the substrate and metal materials with high density and high modulus of elasticity for the scatterer can maximally widen the bandgap and allows for low-frequency sound insulation below 600 Hz. This approach improves the low-frequency sound insulation efficiency of acoustic metamaterials. The results provide important explanations and references for a deeper understanding of the sound insulation mechanism and the effects of different parameters on sound insulation.